Pediatric nasopharyngeal airways expand when exposed to saline. (November 2019) - Bensoussan, Yael; Wolter, Nikolaus E.; Peer, Shazia; Alemu, Robel Z.; Roy, Melissa; Propst, Evan J.
Abstract: Purpose: Nasopharyngeal airways (NPA) are commonly used to relieve upper airway obstruction in children. They must be sized to extend posterior to the tongue base but remain above the epiglottis. To avoid obstruction from nasal secretions, frequent irrigation with saline is required. We hypothesized that NPAs would swell when exposed to saline irrigation. Methods: Twenty-five green Rusch NPA size 12, 14, 16, 18 and 20 Fr were submerged in 2 L of normal saline for 15 days. Tube length, inner diameter, outer diameter and wall thickness were measured on days 1, 2, 3, 4, 5, 10, and 15 and compared using two-way repeated measures ANOVA and paired t-tests with Bonferroni correction. Results: All dimensions increased significantly with exposure to saline. Increases in length, inner diameter, outer diameter and wall thickness were dependent on original tube size (p < 0.05) and duration of exposure to saline (p < 0.001). The increase in tube length was greatest over the first five days. Conclusion: NPAs expand significantly when exposed to saline with the greatest increase in length occurring in the first five days. This could lead to gagging or airway obstruction in small children. Patients with NPAs should be monitored closely for these signs and new materials should be sourced to prevent these issues.